A Computational Approach toward the Enhanced Performance of Graphene–Perovskite Schottky Solar Cells. Issue 3 (9th March 2020) - Lin, Lingyan; Jiang, Linqin; Li, Ping; Li, Xiaoyan; Qiu, Yu
Abstract : A graphene–perovskite Schottky solar cell is numerically analyzed, where the graphene serves as both a front transparent electrode for light transmission and a layer for carrier separation and collection. The influences of the parameters of graphene, perovskite, and back contact are studied to achieve optimized device performance. More details can be found in article number 1901197 by Yu Qiu and co‐workers.